2020
DOI: 10.1016/j.cmi.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Are nontreponemal tests suitable for monitoring syphilis treatment efficacy? Evidence from rabbit infection models

Abstract: Objectives: We aimed to characterize kinetics of non-treponamal antibody titres during the natural course of syphilis and explore their roles in monitoring syphilis treatment efficacy. Methods: Sixty New Zealand white male rabbits were challenged with Nichols or Amoy Treponema pallidum strains, and the rapid plasma reagin (RPR) test was performed to quantify non-treponemal antibody titres during the infection course. Viable T. pallidum in the challenged rabbits was assessed with rabbit infectivity tests. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Indeed, the rabbit that was injected with CDC-SF007, which successfully grew in vivo, did not show any discernible orchitis even when seroreactive and PCR+, while the rabbit with CDC-SF003 developed orchitis beginning in week 6 when an increase in antibody titers was first noted. Consistent with previous studies [9,26,61,64,65], these observations indicate that including additional detection methods for treponemal propagation in rabbits can avoid overlooking an active infection that could inadvertently be cleared by the immune response before treponemal harvest can be performed. Of note, when comparing serology and PCR, both methods generally showed a reactive or positive result at comparable time points post infection for a given rabbit, which aligns with a previous study [61].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the rabbit that was injected with CDC-SF007, which successfully grew in vivo, did not show any discernible orchitis even when seroreactive and PCR+, while the rabbit with CDC-SF003 developed orchitis beginning in week 6 when an increase in antibody titers was first noted. Consistent with previous studies [9,26,61,64,65], these observations indicate that including additional detection methods for treponemal propagation in rabbits can avoid overlooking an active infection that could inadvertently be cleared by the immune response before treponemal harvest can be performed. Of note, when comparing serology and PCR, both methods generally showed a reactive or positive result at comparable time points post infection for a given rabbit, which aligns with a previous study [61].…”
Section: Discussionsupporting
confidence: 89%
“…Our data showed that the RPR titer could decrease more than fourfold before treatment, which means that the treatment success criteria could be achieved without treatment in some patients. In a rabbit model, non-treponemal titers increased after infection and then spontaneously decreased more than fourfold within 6 months even without treatment [ 8 ]. Even after the RPR titer became negative, however, viable T .…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers and clinicians have reported that the nontreponemal titer could change without treatment. In a rabbit model of syphilis infection, the natural course of the nontreponemal titer shows a bell-shaped curve with a longer right tail; the titer increases shortly after inoculation, then decreases gradually, and can become negative even without treatment [ 8 ]. We hypothesized that if nontreponemal titer increases and decreases spontaneously in humans, then pre-treatment changes in nontreponemal titer might affect post-treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recovery from syphilis is traditionally dependent on the detection of nontreponemal rapid plasma reagin titers. However, it was proposed that titers are not as relevant to the prognosis of syphilis as might be expected [ 176 ]. Thus, epitopes in infection phase-dependent antigens are promising to evaluate the recovery of syphilis [ 177 ].…”
Section: Discussionmentioning
confidence: 99%